2014
DOI: 10.1002/embr.201338170
|View full text |Cite
|
Sign up to set email alerts
|

Some like it cold: understanding the survival strategies of psychrophiles

Abstract: Much of the Earth's surface, both marine and terrestrial, is either periodically or permanently cold. Although habitats that are largely or continuously frozen are generally considered to be inhospitable to life, psychrophilic organisms have managed to survive in these environments. This is attributed to their innate adaptive capacity to cope with cold and its associated stresses. Here, we review the various environmental, physiological and molecular adaptations that psychrophilic microorganisms use to thrive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
334
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(375 citation statements)
references
References 84 publications
(142 reference statements)
11
334
0
7
Order By: Relevance
“…3 and 4) within the processing plant 16S rRNA gene amplicons showed that all of the abundantly found genera contained mesophilic psychrotrophs. This is understandable as approximately 80% of the earth is cold, and most of the psychrotolerant microbes (optimal temperatures between 20°C and 25°C) on earth live in fluctuating temperatures (22). The surface samples had high levels of Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4) within the processing plant 16S rRNA gene amplicons showed that all of the abundantly found genera contained mesophilic psychrotrophs. This is understandable as approximately 80% of the earth is cold, and most of the psychrotolerant microbes (optimal temperatures between 20°C and 25°C) on earth live in fluctuating temperatures (22). The surface samples had high levels of Proteobacteria, Bacteroidetes, Firmicutes, and Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, bacteria 594 Iva Tomova et al dominate in many terrestrial Antarctic ecosystems and play essential role in food chains, biogeochemical cycles and mineralization of pollutants Walker 1993, 1995;Aislabie et al 2006Aislabie et al , 2009Franzmann et al 1997;Tindall 2004;Walker 2005;Tomova et al 2014;Tytgat et al 2014;Vasileva−Tonkova and Gesheva 2004). Psychrophilic and psychrotolerant microorganisms have developed various adaptations to extreme environments through physiological and ecological mecha− nisms (Russell 1998;De Maayer et al 2014). Enzymes are an essential target for adaptation of microorganisms to extreme environments with considerable poten− tial for industrial application (Feller and Gerday 2003;Cavicchioli et al 2011;Kumar et al 2011;Gesheva and Vasileva−Tonkova 2012;Loperena et al 2012;Tropeano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…−20 °C in sea ice) to a maximum temperature of 20 °C [3]. Roughly 80 % of our planet's biosphere is at temperatures below 5 °C, which includes most of the world's oceans (70 % of the Earth's surface), sea ice, Antarctica, parts of North America and Europe, the deep-sea, mountain regions, as well as the mesosphere and stratosphere [4]. Thus, most microorganisms on Earth can be considered to be psychrophiles.…”
Section: -2506mentioning
confidence: 99%